Unravelling gendered practices in the public water sector in Nepal - Shrestha, Gitta; Clement, Floriane (IWA Publishing, 2019)
Despite decades of gender mainstreaming in the water sector, a wide gap between policy commitments and outcomes remains. This study aims at offering a fresh perspective on such policy gaps, by analysing how gendered discourses, institutions and professional culture contribute to policy gaps. We rely on a conceptual framework originally developed for analysing strategic change, which is used to analyse gender in the public water sector in Nepal. Our analysis relies on a review of national water policies and a series of semi-structured interviews with male and female water professionals from several public agencies. Our findings evidence how dominant discourses, formal rules and professional culture intersect to support and reproduce hegemonic masculine attitudes and practices of water professionals. Such attitudes and practices in turn favour a technocratic implementation of policy measures. We argue that gender equality policy initiatives in the water sector have overly focused on local level formal institutions and have not adequately considered the effects of masculine discourses, norms and culture to be effective in making progress towards gender equity. We conclude with policy recommendations.